The Mode of Pretransplant Dialysis Does Not Affect Postrenal Transplant Outcomes in African Americans - Amit Sharma; Todd L. Teigeler; Martha Behnke; Adrian Cotterell; Robert Fisher; Anne King; Todd Gehr; Marc Posner (Journal of Transplantation)
Background. In previous reports with a majority of Caucasian patients, peritoneal dialysis (PD) before kidney transplantation has been associated with poor outcomes and higher rates of graft thrombosis and infectious complications than hemodialysis (HD). We report our experience on the outcomes of prerenal transplant peritoneal dialysis in predominantly (73%) African American patient population. Methods. A retrospective data analysis of 401 kidney transplants performed at our center from 2000 to 2006 was performed. Adult recipients with at least three months of pretransplant HD or PD were included. Results. There were 339 patients on HD and 62 patients on PD. There was no difference in graft (P=0.51) and patient survival (P=0.52) at 1, 3, and 5-years. Patients on HD were more likely to experience delayed graft function than PD (38.8% versus 17.7%, P<0.005). There was no difference in the incidence of vascular thrombosis or posttransplant infectious complications. When only the African American patients in the two groups were compared, there were no differences in graft or patient survival. Conclusions. Pretransplant peritoneal dialysis is associated with excellent patient and renal allograft outcomes in African Americans and does not predispose them to an increased risk of infectious or thrombotic complications.